Cocaine Reduces the Neuronal Population While Upregulating Dopamine D2-Receptor-Expressing Neurons in Brain Reward Regions: Sex-Effects - Clare, Kevin; Pan, Chelsea; Kim, Gloria; Park, Kicheon; Zhao, Juan; Volkow, Nora D.; Lin, Zhicheng; Du, Congwu (Frontiers in Pharmacology, 2021)
Addiction to cocaine is associated with dysfunction of the dopamine mesocortical system including impaired dopamine-2 receptor (D2r) signaling. However, the effects of chronic cocaine on neuronal adaptations in this system have not been systematically examined and data available is mostly from males. Here, we investigated changes in the total neuronal density and relative concentration of D2r expressing neurons in the medial prefrontal cortex (mPFC), dorsal striatum (Dstr), nucleus accumbens (NAc), and ventral tegmental area (VTA) in both male and female mice passively exposed to cocaine for two weeks. In parallel experiments, we measured mRNA levels for Drd2 and for opioid peptides (mPenk and mPdyn). Through a combination of large field of view fluorescent imaging with BAC transgenic D2-eGFP mice and immunostaining, we observed that cocaine exposed mice had a higher density of D2r-positive cells that was most prominent in mPFC and VTA and larger for females than for males amidst an overall significant decrease in neuronal density (measured with NeuN) in both sexes. However, increases in Drd2 mRNA levels with cocaine were only observed in mPFC and Dstr in females, which might reflect the limited sensitivity of the method. Our findings, which contrast with previous findings of cocaine-induced downregulation of D2r binding availability, could reflect a phenotypic shift in neurons that did not previously express Drd2 and merits further investigation. Additionally, the neuronal loss particularly in mPFC with chronic cocaine might contribute to the cognitive impairments observed with cocaine use disorder.